Ionotropic and metabotropic responses by alpha 7 nicotinic acetylcholine receptors - Patricia Sinclair; Nadine Kabbani (Elsevier, 2023)
Nicotinic acetylcholine receptors (nAChRs) belong to a superfamily of cys-loop receptors characterized by the assembly of five subunits into a multi-protein channel complex. Ligand binding to nAChRs activates rapid allosteric transitions of the receptor leading to channel opening and ion flux in neuronal and non-neuronal cell. Thus, while ionotropic properties of nAChRs are well recognized, less is known about ligand-mediated intracellular metabotropic signaling responses. Studies in neural and non-neural cells confirm ionotropic and metabotropic channel responses following ligand binding. In this review we summarize evidence on the existence of ionotropic and metabotropic signaling responses by homopentameric α7 nAChRs in various cell types. We explore how coordinated calcium entry through the ion channel and calcium release from nearby stores gives rise to signaling important for the modulation of cytoskeletal motility and cell growth. Amino acid residues for intracellular protein binding within the α7 nAChR support engagement in metabotropic responses including signaling through heterotrimeric G proteins in neural and immune cells. Understanding the dual properties of ionotropic and metabotropic nAChR responses is essential in advancing drug development for the treatment of various human disease.